Cell growth-dependent subcellular localization of p8 - Valacco, Maria Pia (2006)
p8 is a stress-induced protein, biochemically related to the architectural factor HMG-I/Y, overexpressed in many cancers and required for tumor expansion. The molecular mechanisms by which p8 may exert its effect in aspects of growth is unknown. Using immunocytochemistry, we found that p8 presents nuclear localization in sub-confluent cells, but it localizes throughout the whole cell in high density grown cells. Cells arrested in Go/G1, either by serum deprivation or by hydroxyurea treatment, show a nucleo-cytoplasmic localization of p8, whether in the rest of the cell cycle stages of actively dividing cells the localization is nuclear. A comparison of p8 sequences from human to fly predicts a conserved bipartite nuclear localization sequence (NLS). The putative NLS has been demonstrated to be functional, since nuclear import is energy dependent (inhibited by sodium azide plus 2-deoxyglucose), and fusion proteins GFP-p8 and GFP-NLSp8 localize to the nucleus, whereas GFP-p8NLSmut in which with Lys 65, 69, 76, and 77 mutated to Ala localized to the whole cell. p8 localization does not involve the CRM1 transporter, since it is insensitive to leptomycin B. Inhibitors of MARK pathways did not affect p8 subcellular localization. The inhibition of deacetylation with Trichostatin A promotes cytoplasmic accumulation of p8. The results suggest that p8 growth stage-dependent localization is regulated by acetylation, that p8 is not free within the cell but forming part of a complex and that it may exert a role in both subcellular localizations.